The Accounting Environment And The Development Of Financial Reports In Commercial Banks Of Pakistan - Kasi, Mrs Arifa; Barkat, Nazia; Khaliq, Asma Abdul; Ahmed, Syed Khalil; Iqbal, Asif (The journal of contemporary issues in business and government, 2021)
The accounting environment plays a vital role in the banking sector. The present paper explores the predictive power of the accounting environment in developing financial reports. The commercial banks of Pakistan are selected as the study context. The study employs a deductive approach which is handled through a path analysis. The findings of the study show a significant and positive effect of the accounting environment’s constructs like liquidity, financial leverage (FL), profitability, earnings management (EM), corporate governance (CG) and company life cycle (CLC) on the accounting environment (AE) in the commercial banks of Pakistan. The findings of a study would further provide the guidelines to policymakers and planners in developing the conducive AE, which would increase the profitability and CLC. Moreover, the study outcomes would contribute to the domain literature, i.e. finance, management and banking in the context of financial reports development.